Exploring the Ability of Early Childhood Teachers to Carry Out Assessment - Anita Yus; Dwi Septi Anjas Wulan; Winda Widya Sari; Salim Salim (BIRCU, 2021)
This study aims to determine how the application of authentic assessment in kindergarten by assessing the adequacy of aspects of assessment and implementation of assessment instruments. Research respondents are kindergarten teachers in North Sumatra Province, totaling 65 people. The data was collected using a questionnaire and document analysis, which consisted of lesson plans, children's work that had been analyzed by the teacher and the assessment instruments that had been used by the teacher. Data were analyzed using descriptive statistical techniques and qualitative analysis by linking existing data to obtain meaning. The results of the analysis showed that: (1) there were 100% of kindergarten teachers who stated that they had carried out an assessment every time they carried out the teaching process but most had difficulty indicating the assessment instrument used, (2) 97% of kindergarten teachers only used a checklist to collect developmental assessment data and children's learning activities by putting a check mark on one of the scales consisting of